2020
DOI: 10.3390/biomedicines8030054
|View full text |Cite
|
Sign up to set email alerts
|

Outer Nuclear Layer Damage for Detection of Early Retinal Toxicity of Hydroxychloroquine

Abstract: In hydroxychloroquine (HCQ) retinopathy, early detection of asymptomatic retinal changes and the interruption of the drug are essential to prevent permanent vision loss. Our purpose was to investigate the roles of ganglion cell layer (GCL) and outer nuclear layer (ONL) thicknesses measured by optical coherence tomography (OCT) in the early diagnosis of retinopathy. One hundred and fourteen eyes of 76 individuals with HCQ treatment were enrolled in the study (42 eyes with impaired visual field (VF) and 72 eyes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
4
6
0
Order By: Relevance
“…To the best of our knowledge, there are no other studies in the current literature that show an anatomically damaged retinal layer in Tacrolimus-associated maculopathy. This finding is consistent with the recent results of Casado et al [ 13 ], that studied retinal damage in individuals with Hydroxychloroquine treatment. They found that ONL thickness was significantly decreased in patients taking Hydroxychloroquine compared with the control group.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…To the best of our knowledge, there are no other studies in the current literature that show an anatomically damaged retinal layer in Tacrolimus-associated maculopathy. This finding is consistent with the recent results of Casado et al [ 13 ], that studied retinal damage in individuals with Hydroxychloroquine treatment. They found that ONL thickness was significantly decreased in patients taking Hydroxychloroquine compared with the control group.…”
Section: Discussionsupporting
confidence: 94%
“…The case reported by Taehuk et al [ 9 ] and the study of Casado et al [ 13 ] were key in our suspect diagnosis. The elevation of Tacrolimus plasma level in our patients directed us toward the hypothesis of Tacrolimus induced maculopathy.…”
Section: Discussionmentioning
confidence: 66%
“…Life threatening arrhythmias associated with CQ and HCQ appear to be rare but if these drugs were to be used much more extensively then caution and appropriate monitoring are necessary [36,37]. Patients and their physicians prescribing HCQ need to be keenly aware of retinal toxicity risks and the importance of regular screening, and ophthalmologists who see these patients should keep retinal toxicity in the front of their minds [38][39][40]. However, chronic use of HCQ can result in an acquired lysosomal storage disorder, leading to a drug-induced cardiomyopathy characterized by concentric hypertrophy and conduction abnormalities associated with increased adverse clinical outcomes and mortality [41].…”
Section: Discussionmentioning
confidence: 99%
“…These changes are visible in SD-OCT. The disruption of the ellipsoid zone and the loss of the outer nuclear layer (ONL) 11 , 19 cause a collapse of the parafoveal retina, which can lead to a “flying saucer” appearance of the fovea 20 . These structural changes in the outer retina usually correlate with functional changes shown in multifocal electroretinograms (mERGs) and changes in the visual field 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%